Effectiveness Of Capital Adequacy Ratio And Problem Loans In Affecting Stock Return: A Roa Moderation Perspective In National Private Commercial Banks - Atika Purnamasari; Deta Oktavia; Sumaryo; Petty Aprilia Sari (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL) on stock returns, with Return on Assets (ROA) as a moderating variable in banking companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with regression analysis and Moderated Regression Analysis (MRA). The data used are secondary data in the form of annual financial reports for the 2022–2024 period, processed using statistical software. Tests were conducted using partial tests (t-tests), simultaneous tests (F-tests), and the coefficient of determination (R²) to determine the model's ability to explain the dependent variable. The results show that CAR has no effect on stock returns, while NPL has a negative effect on stock returns. In the moderation test, ROA was able to strengthen the effect of CAR on stock returns, but failed to moderate the effect of NPL on stock returns. These findings indicate that investors are more concerned with a bank's ability to generate profits and manage capital efficiently than solely considering capital adequacy or credit risk separately. Thus, the combination of capital strength and profitability is an important factor in increasing investor confidence in the capital market.